Identification of Xylem Occlusions Occurring in Cut Clematis (Clematis L., fam. Ranunculaceae Juss.) Stems during Their Vase Life - Agata Jedrzejuk; Julia Rochala; Jacek Zakrzewski; Julita Rabiza-Świder (The Scientific World Journal)
During the vase life of cut stems obstruction of xylem vessels occurs due to microbial growth, formation of tyloses, deposition of materials in the lumen of xylem vessels and the presence of air emboli in the vascular system. Such obstructions may restrict water uptake and its transport towards upwards thus lowering their ornamental value and longevity of cut flowers. Clematis is a very attractive plant material which may be used as cut flower in floral compositions. Nothing is known about the histochemical or cytological nature of xylem blockages occurring in cut stems of this plant. This study shows that in clematis, tyloses are the main source of occlusions, although bacteria and some amorphic substances may also appear inside the vessels. A preservative composed of 200 mg dm−3 8-HQC (8-hydroxyquinolin citrate) and 2% sucrose arrested bacterial development and the growth of tyloses. This information can be helpful in the development of new treatments to improve keeping qualities of cut clematis stems.